Influence of Anomalous Upwelling on the Water Mass of South Java during Two Positive Indian Ocean Dipole in 2015 and 2019 - Herlambang, Dominikus Krisna; Iskandar, Iskhaq (Jurnal Penelitian Pendidikan IPA, 2023)
Upwelling is a phenomenon that often occurs in the ocean. Upwelling can be interpreted as the process of rising sea water masses from below the surface to the surface due to the vacancy of sea water masses at the surface. The upwelling phenomenon will cause many anomalies that have a direct impact on ocean dynamics, one of which is the dynamics that occur in the waters south of Java. The formation of the coastal upwelling phenomenon in the waters south of Java in 2015 and 2019 was the cause of the active Positive IOD in both years. By carrying out time series analysis and spatial data visualization processes as well as correlation methods to determine the relationship between parameters, this research aims to discuss and find out about the influence of coastal upwelling dynamics on the waters of southern Java in 2015 and 2019. The results obtained from this research show that the coastal upwelling phenomenon formed in 2015 and 2019 along the waters of southern Java resulted anomalies in dynamic patterns in the form of decreasing sea surface temperatures and increasing chlorophyll-a concentrations